Analisa Penyandian File Dokumen Kriptografi Menggunakan Advanced Encryption Standard (AES) - Terisha Sheline Shazhaq; Muhlis Tahir; Khoirul Amin Abidin; Vivia Auria; Diana Iis Maulidia; Dwi Fatkhul Mu’in; Moh Khoiruddin (Jurnal Kendali Teknik dan Sains, 2023)
(Cryptography Advanced Encryption Standard (AES) for File Document Encryption). Advanced Encryption Standard (AES) is a cryptographic algorithms as a standard symmetric key encryption algorithm that used in current time. AES 128 has 1 blok plaintext with 128 bit sized, where in the process of cryptographic algorithms, first the plaintext is converted into hexadecimal-sized 4 x 4 matrices called the state, where each element of state has 1 byte size. The process of encryption on AES is the transformation towards the state repeatedly in the 10th round. Each round of AES requires one key result of the key generation using 2 basic transformation, i.e. substitution and transformation. AES encryption using 4 transformation by the following sequence: subbytes, shiftrows, mixcolumns, and addroundkey. On the other hand, the process of decryption is using the inverse of all the basic transformation of AES algorithm, except addroundkey. Therefore, the sequence of transformation on the decription is invshiftrows, invsubbytes, invmixcolumns, and addroundkey. In the data text, the encryption process is initiated with convertion the data text into ASCII code in hexadecimal numbers that are molded into the matrix 4 x 4 bytes. Next, do some basic transformation such as subbytes, shiftrows, mixcolumns, and addroundkey. However, when performing the transformation, the processed data on every trasformation is in the form of binary data obtained from the hexadecimal matrix. AES 128 bit cryptography have room 2128 keys which is a tremendous value and is considered secure to use to avoid the brute force attack.